2000
DOI: 10.21273/hortsci.35.6.1163
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Rooting and Subsequent Survival of Two Clones of a Cold-tolerant Eucalyptus grandis × E. nitens Hybrid

Abstract: Multiple shoots of two Eucalyptus grandis Hill ex Maid. × E. nitens (Deane & Maid.) Maid. clones (GN121 and GN107) generated from axillary buds were used for in vitro rooting studies. The highest rooting rates in clones GN121 (75%) and GN107 (65%) were achieved on modified 1/4-strength Murashige and Skoog (MS) (1962) medium (Ca2+ and Mg2+ levels as for 3/4-strength MS), 0.5 μm IBA, 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 12 publications
(14 reference statements)
0
9
0
4
Order By: Relevance
“…After 6 wk of culture, the simultaneous presence of IAA and 2iP at 1.14 and 1.96μM, respectively, promoted the highest shoot multiplication (3.8 shoots per explant). Synergistic effect of cytokinins and auxins in axillary shoot proliferation has been also reported in Rosa roxburghii (Ma et al 1996), in rootstock selections of Pirus communis and Pirus betulifolia (Yeo and Reed 1995), in Eucalyptus grandis x E. nitens (Mokotedi et al 2000), and in Myrtus communis (Ruffoni et al 1994). The best result in terms of shoot length was also obtained from the medium augmented with 1.14μM IAA and 1.96μM 2iP, although the effectiveness of this treatment did not differ significantly from that of the medium deprived of growth regulators and from that of the other media containing 2iP alone (3.92 or 15.68μM 2iP) or in combination with IAA (1.14μM IAA and 15.68μM 2iP).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…After 6 wk of culture, the simultaneous presence of IAA and 2iP at 1.14 and 1.96μM, respectively, promoted the highest shoot multiplication (3.8 shoots per explant). Synergistic effect of cytokinins and auxins in axillary shoot proliferation has been also reported in Rosa roxburghii (Ma et al 1996), in rootstock selections of Pirus communis and Pirus betulifolia (Yeo and Reed 1995), in Eucalyptus grandis x E. nitens (Mokotedi et al 2000), and in Myrtus communis (Ruffoni et al 1994). The best result in terms of shoot length was also obtained from the medium augmented with 1.14μM IAA and 1.96μM 2iP, although the effectiveness of this treatment did not differ significantly from that of the medium deprived of growth regulators and from that of the other media containing 2iP alone (3.92 or 15.68μM 2iP) or in combination with IAA (1.14μM IAA and 15.68μM 2iP).…”
Section: Resultsmentioning
confidence: 79%
“…There are other reports of IAA and IBA being effective in stimulating adventitious root formation in other Myrtaceae such as Myrtus communis (Ruffoni et al 1994;Scarpa et al 2000), Eucalyptus ficifolia (de Fossard and Bourne 1976), Eucalyptus grandis X E. nitens (Mokotedi et al 2000), Eucalyptus globules, and E. saligna (Foçaga and Fett-Neto 2005). The present study also demonstrated the superiority of IAA and IBA over NAA in the induced development of adventitious root formation.…”
Section: Resultsmentioning
confidence: 93%
“…0239/4820) located 5 km from the experimental site (Figure 1). Micropropagated saplings of a clone of E. grandis × E. nitens were produced in our laboratory (Mokotedi et al 2000) whilst macropropagated E. grandis × E. nitens of the same clone, as well as seed-propagated E. grandis and E. nitens of comparable age, were obtained from Mountain Home Nursery (Mondi Business Paper, Hilton, Pietermaritzburg). After acclimatisation, all plantlets were maintained in their containers according to standard…”
Section: Study Site and Plant Materialsmentioning
confidence: 99%
“…In terms of micropropagation, axillary bud proliferation is generally the preferred choice (reviews by Jones and Van Staden 1997;Watt et al 2003;de Assis et al 2004) and, together with some specific mini-cutting techniques (e.g. Schwambach et al 2008), the only viable method for the propagation of difficult-to-root clones (Yasodha et al 2004;Mokotedi et al 2000;George et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, roots of micropropagated plants established just below the soil surface as a few I-beam shaped roots, whereas seedling plants developed numerous T-beam shaped roots, which were significantly more resistant to uprooting than the micropropagated ones (Mokotedi et al 2010). That study employed the standard, routinely-used protocol in our laboratories, adapted for the clone for maximum multiplication, elongation, rooting and acclimation yields, with specific PGRs for each of the in vitro stages (Mokotedi et al 2000). The results from that field work may, therefore, be explained by the influences of the supplied phytohormones pre-and post-rooting.…”
Section: Introductionmentioning
confidence: 99%